Refiguring Christ, the true vine: an exploration of an Ἐγώ εἰμι saying using Ricoeur's concept of ‘metaphor’ - Belt, Ruben van de (Scriptura, 2017)
Paul Ricoeur’s understanding of metaphorical language is of great importance in reflection of biblical hermeneutics, not the least when it comes to the parables of Jesus. This article first explores Ricoeur’s conception of metaphor, and moves to apply it to metaphor Jesus uses in the seventh Johannine “I am” saying (John 15:1-8). It is argued that the relevance of metaphor understood along the lines of Ricoeur lies therein that it draws focus to the necessity of creative and ‘living’ metaphor for proper speech about Christ, even though the ‘thing’ will always have yet another meaning. A condition for such metaphorical language is unpretentious knowledge of both the text and context of the metaphors applied to Christ in the New Testament—as well as those applied to the godhead in the Bible as a whole— and a firm understanding of the context of the contemporary reader. To aim is to sketch some lines for a metaphorical Christology that brings the Gospel close to believers today.